State of research in automatic as-built modelling. Issue 2 (April 2015) - Pătrăucean, Viorica; Armeni, Iro; Nahangi, Mohammad; Yeung, Jamie; Brilakis, Ioannis; Haas, Carl
Abstract Building Information Models (BIMs) are becoming the official standard in the construction industry for encoding, reusing, and exchanging information about structural assets. Automatically generating such representations for existing assets stirs up the interest of various industrial, academic, and governmental parties, as it is expected to have a high economic impact. The purpose of this paper is to provide a general overview of the as-built modelling process, with focus on the geometric modelling side. Relevant works from the Computer Vision, Geometry Processing, and Civil Engineering communities are presented and compared in terms of their potential to lead to automatic as-built modelling.